Innovation in Education Care Program on People’s Schooling Participation at LAZ DQ of Sidoarjo - Salsabila, Nada Rakhima; Mega Paksi, Girindra (Management of Zakat and Waqf Journal (MAZAWA), 2025)
This study describes a new strategy for generating human development effects through the education care program of LAZ Dompet Al-Qur'an Indonesia Sidoarjo. The distribution of zakat funds for scholarship programs is only incidental, with no monitoring for human development. This study is descriptive qualitative, with the researcher acting as the key instrument. Primary data was obtained through interviews with zakat institution administrators and several beneficiaries. The results show that the Education Program has succeeded in increasing community participation in contributing to support the education of underprivileged youth in Indonesia. Institutions are advised to mobilize volunteers as mentors for scholarship recipients who need additional academic support, develop educational applications that can be accessed by parents and students to facilitate the learning process, and emphasize the importance of contributing to the success of Indonesian youth education, especially through donations to LAZ.  The recommendations from this research serve as a reference for institutions to strengthen public trust and manage prospective scholarship recipients, thereby ensuring the long-term sustainability of the Education Program